Quality of Instrument Assessment of Learning Outcomes Based Curriculum 2013 Class X SMAN in Kendal - Nurjanah, Ayu Ika; Rudyatmi, Ely; Susilowati, Sri Mulyani Endang (Journal of Biology Education, 2019)
One important component of the curriculum in 2013 is a competency-based assessment. This assessment is not only seen from the final result, but also how the processes that occur during learning. Assessment is done using instruments varies. Instruments' knowledge, attitudes, and skills that exist have not analyzed the quality but it is used by teachers in conducting the evaluation. The purpose of this study was to analyze the quality of assessment instruments UKK, attitude observation sheets, and assessment sheets used in practice test Class X SMAN biology teacher in Kendal. The quantitative data in the form of the level of difficulty, distinguishing, distractor effectiveness, and reliability matter UKK. Qualitative data in the form of conformity UKK, observation sheets attitude, and practice tests assessment sheet in terms of material, construction, and language. The results showed that the quality of qualitative UKK is 45% good and 55% about the problem should be corrected. Qualitatively UKK quality is good and 75% about 25% is not good. Observation sheet quality is pretty good 83% and 17% unfavorable. Sheet quality assessment practice test is 83% good and 17% poor.